Respostas

A melhor resposta!
  • Usuário do Brainly
2014-09-03T00:21:34-03:00
y= x^{2} -2x-24

 x^{2} -2x-24=0

x= \frac{-b\pm \sqrt{b^2-4ac} }{2a}

x= \frac{2\pm \sqrt{4+96} }{2} = \frac{2\pm \sqrt{100} }{2}

x= \frac{2\pm10}{2}

x'= \frac{2+10}{2} = \frac{12}{2}=6

x"= \frac{2-10}{2}=- \frac{8}{2} =-4

S={-4,8}

b)

f(x)=x²-4x+5
x²-4x+5=0
Δ=b²-4ac
Δ=16-20
Δ=-4
como Δ deu negativo
S=\emptyset  ou  {  }

c)
f(x)=x²-10x+25
x²-10x+25=0
Δ=b²-4ac
Δ=100-100
Δ=0
x=- \frac{b}{2a} = \frac{10}{2} =5

x'+x"=5

S={5}
2 5 2
  • Usuário do Brainly
2014-09-03T01:09:53-03:00
A) y=x^2-2x-24

y=0

x^2-2x-24=0

\Delta=(-2)^2-4\cdot1\cdot(-24)=4+96=100

x=\dfrac{-(-2)\pm\sqrt{100}}{2}=\dfrac{2\pm10}{2}=1\pm5

x'=1+5=6

x"=1-5=-4

As raízes são -4 e 6.


b) f(x)=x^2-4x+5

f(x)=0

x^2-4x+5=0

\Delta=(-4)^2-4\cdot1\cdot5=16-20=-4

\Delta<0

Não há raízes reais.


c) g(x)=x^2-10x+25

g(x)=0

x^2-10x+25=0

\Delta=(-10)^2-4\cdot1\cdot25=100-100=0

x=\dfrac{-(-10)\pm\sqrt{0}}{2}=\dfrac{10}{2}

x'=x"=5

A única raiz é 5.

Outra maneira:

x^2-10x+25=0

(x-5)^2=0

x-5=0

x=5, como antes.

1 5 1